PENYELESAIAN SENGKETA MASALAH PIPA SALURAN AIR ANTARA KONSUMEN DENGAN PERUSAHAAN AIR MINUM DAERAH (PDAM) OLEH BPSK KOTA BUKITTINGGI - Sarah Rasyikah; Anggun Lestari Suryamizon; Jasman Nazar (Ensiklopedia of Journal, 2023)
The settlement of disputes between consumers and the Regional Drinking Water Company Tirta Jam Gadang Bukittinggi is contained in Case Number 002/P/BPSK-BKT/2022. The dispute occurred because there was a pipe leak, resulting in losses for consumers. Consumer rights are not fulfilled as stipulated by the Consumer Protection Act. Consumer complaints to business actors have never been responded to. So the consumer complained to the Bukittinggi City Consumer Dispute Settlement Body. Research objectives 1) To find out the resolution of disputes over water pipeline problems between consumers and the Regional Drinking Water Company in the City of Bukittinggi. 2) To find out the obstacles in resolving water pipe disputes between consumers and the Regional Drinking Water Company in the City of Bukittinggi. Descriptive legal research uses an empirical juridical approach. This study concludes that 1) Dispute resolution by BPSK Kota Bukittinggi is carried out by means of mediation which aims to reconcile the parties. Regional drinking water company Tirta Jam Gadang as a business actor apologizes and provides compensation for consumer losses. The compensation given is to repair the water pipes and cut water payments within a period of 30 years. 2) The internal constraints are in the form of regulatory changes, lack of operational costs, inadequate facilities and infrastructure. External constraints include the lack of public legal knowledge and the parties not being present at the trial at the Consumer Dispute Settlement Body for the City of Bukittinggi.